Variability of allergens in commercial fish extracts for skin prick testing. Issue 7 (15th April 2019) - Ruethers, Thimo; Taki, Aya C.; Nugraha, Roni; Cao, Trúc T.; Koeberl, Martina; Kamath, Sandip D.; Williamson, Nicholas A.; O'Callaghan, Sean; Nie, Shuai; Mehr, Sam S.; Campbell, Dianne E.; Lopata, Andreas L.
Abstract: Background: Commercial allergen extracts for allergy skin prick testing (SPT) are widely used for diagnosing fish allergy. However, there is currently no regulatory requirement for standardization of protein and allergen content, potentially impacting the diagnostic reliability of SPTs. We therefore sought to analyse commercial fish extracts for the presence and concentration of fish proteins and in vitro IgE reactivity using serum from fish‐allergic patients. Methods: Twenty‐six commercial fish extracts from five different manufacturers were examined. The protein concentrations were determined, protein compositions analysed by mass spectrometry, followed by SDS‐PAGE and subsequent immunoblotting with antibodies detecting 4 fish allergens (parvalbumin, tropomyosin, aldolase and collagen). IgE‐reactive proteins were identified using serum from 16 children with confirmed IgE‐mediated fish allergy, with focus on cod, tuna and salmon extracts. Results: The total protein, allergen concentration and IgE reactivity of the commercial extracts varied over 10‐fold between different manufacturers and fish species. The major fish allergen parvalbumin was not detected by immunoblotting in 6/26 extracts. In 7/12 extracts, five known fish allergens were detected by mass spectrometry. For cod and tuna, almost 70% of patients demonstrated the strongest IgE reactivity to collagen, tropomyosin, aldolase A or β‐enolase but not parvalbumin. Conclusions: Commercial fish extracts often contain insufficient amounts of important allergens including parvalbumin and collagen, resulting in low IgE reactivity. A comprehensive proteomic approach for the evaluation of SPT extracts for their utility in allergy diagnostics is presented. There is an urgent need for standardized allergen extracts, which will improve the diagnosis and management of fish allergy. Abstract : Commercial skin prick test (SPT) extracts often contain insufficient amounts of important fish allergens, resulting in low IgE reactivity. Collagen, tropomyosin and aldolase A are of under‐recognized importance for the diagnosis of fish allergy. Understanding the molecular allergology of SPT allergen extracts is essential for best diagnostics.